Autumn sonata [videorecording (DVD)] - Bergman, Ingmar, 1918-2007; Bergman, Ingrid, 1915-1982; Ullmann, Liv (Criterion collection, 1999)
An international concert pianist visits her grown daughter after a seven-year absence. Aching with the memory of her mother's neglect, the introverted daughter explodes into a rage and the reunion turns into a shattering confrontation.